(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Commercial banks by credit to give further expanding They are going . period development with Shahdam step throw for the purpose and competition to the fight endure give in receiving own service types multiplication and development condition . This in turn commerce banks private capital national and international standards to the level zoom in according to scientific and practical importance has was research take to go question Credit​​ operations done in increasing problematic of loans to the surface their arrival , accounting account international standards requirements based on order to put necessity as is putting . This out of necessity come out , commercial in banks loans according to pay and probable losses reserves processes account improvement current from issues one is considered .